2017
DOI: 10.1177/1756285617722347
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for autoimmune encephalitis

Abstract: Autoimmune encephalitis is one of the most rapidly growing research topics in neurology. Along with discoveries of novel antibodies associated with the disease, clinical experience and outcomes with diverse immunotherapeutic agents in the treatment of autoimmune encephalitis are accumulating. Retrospective observations indicate that early aggressive treatment is associated with better functional outcomes and fewer relapses. Immune response to first-line immunotherapeutic agents (corticosteroids, intravenous im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
216
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 204 publications
(229 citation statements)
references
References 153 publications
(250 reference statements)
5
216
0
8
Order By: Relevance
“…Autoimmune encephalitis (AE) is an emerging type of immune‐mediated neurologic disorder. The clinical manifestations of AE are variable and depend on the presence of specific types of autoantibodies . Although most patients are responsive to immunotherapeutic agents, a substantial number of patients are intractable to first‐ and second‐line immunotherapies .…”
mentioning
confidence: 99%
“…Autoimmune encephalitis (AE) is an emerging type of immune‐mediated neurologic disorder. The clinical manifestations of AE are variable and depend on the presence of specific types of autoantibodies . Although most patients are responsive to immunotherapeutic agents, a substantial number of patients are intractable to first‐ and second‐line immunotherapies .…”
mentioning
confidence: 99%
“…If patients do not show a response in the first 2 weeks, the second line of treatment is rituximab, alone or combined with cyclophosphamide . Rituximab depletes B cells; however, its effectiveness over cyclophosphamide (a strong immunosuppressant) is not yet clear .…”
Section: Resultsmentioning
confidence: 99%
“…24,70 If patients do not show a response in the first 2 weeks, the second line of treatment is rituximab, alone or combined with cyclophosphamide. 71,72 Rituximab depletes B cells; however, its effectiveness over cyclophosphamide (a strong immunosuppressant) is not yet clear. 73 Lee et al reported on the efficacy and safety of rituximab as a second-line immunotherapy for AIE in 161 patients in which rituximab was associated with improvement on functional outcomes measured on the modified Rankin Scale.…”
Section: Advances In Treatmentmentioning
confidence: 99%
“…Cyclophosphamide is considered a high-risk drug with various serious side effects, Rituximab could be a preferable agent. However, Cyclophosphamide is easily accessible and of lower cost than Rituximab [21]. It is not typically used in autoimmune neurological diseases and there are no accepted evidence based guidelines for dosing of Cyclophosphamide in anti-NMDAR encephalitis.…”
Section: Discussionmentioning
confidence: 99%